На солнечной стороне улицы: [роман] / Дина Рубина - Рубина Дина Ильинична (Эксмо, 2011)
Экземпляры: ф.19 (2012) / Инвентарный номер: 48544 / Цена: / Сис.шифр: 84.2Рос6 / Авт.знак: Р 82 / ББК: 84(2Рос=Рус)6